Economic and monetary unions, regional trade and ıntegration: a case study on West African Economic and Monetary Union - Moussa, Abobakarı (My University, 2018)
Bu tezde, Ekonomik ve Parasal Birlikleri ve Batı Afrika Ekonomik ve Parasal Birliğinin(WAEMU) kurulmasının bölgesel ticaret tanıtımına ve entegrasyona nasıl katkıda bulunduğuincelenecektir. Daha spesifik olarak, Batı Afrika para biriminin (CFA) ticaret üzerindeki etkisiniaraştırıyor. WAEMU üyeleri arasında ticarete diğerlerinden daha açık olan ve üyelik bakımındandiğerlerinden Mali, Senegal ve Togo'ya göre daha fazla fayda sağlayan bazı kişiler var. Örneğin,ağırlık modelini kullanan ampirik sonuçlar, aynı para birimini paylaşan ülkelerin - Batı AfrikaCFA - ticaret yaptıkları ülkelerin, diğerlerinden iki kat fazla (2.23) ticaret yaptıklarınıgöstermektedir; bu, ekonomik açıdan ve statik olarak önemlidir. Buna ek olarak, WAEMUülkelerinin ayrıcalıklı ticaret ortağının ticaretinin üç katından fazla olduğu (3.67) Asya ülkeleriolduğunu görüyoruz. Buna ek olarak, bitişikliğin, tarihsel ve kültürel bağların ikili ticareti vebölgesel bütünleşmeyi teşvik ettiğine dair güçlü kanıtlar buluyoruz. Örneğin, tarihi ve kültürelbağları paylaşan ülkeler arasında % 51.7 daha fazla değişim gerçekleşir. Yerçekimi modelinin yanısıra Zivot-Andrews (1992) Yapısal Kırılmayla Birim Kök Testi ve WAEMU üyelerinin az çokaynı iş döngüsüne sahip olduklarını buluyoruz. Sürdürülebilirlik ve daha açık ekonomiler için,WAEMU üye ülkelerinin makroekonomik yakınsama kriterlerine saygı gösterilmesi ve ayrıcaüretken kapasitelerin oluşturulması zorunludur. Bölgesel entegrasyonu güçlendirmek için BatıAfrika Raylı Geçiş Projesinin tamamlanması da çok önemlidir.

This dissertation examines the Economic and Monetary Unions and how the establishment of WestAfrican Economic and Monetary Union (WAEMU) contributes to regional trade promotion andintegration. More specifically, it explores the effect of West African currency (CFA) on trade. WithinWAEMU members, there are some countries who are more open to trade than others and also benefitmore from the membership. Countries like Mali, Senegal and Togo can be given as examples.Empirical findings using gravity model suggests that countries sharing the same currency - WestAfrica CFA – trade over two times (2.23) as much between them than with others which iseconomically meaningful and statistically significant. In addition, we find that the privileged tradepartner of WAEMU countries are Asian countries with whom they trade more than three times (3.67)than with the rest of the world. Furthermore, we find a strong evidence showing that contiguity andhistorical and cultural links encourage bilateral trade and regional integration. It is observed thatcountries sharing historical and cultural links trade 51.7% more with each other. Besides the gravitymodel, we use Zivot-Andrews (1992) unit root test with structural break and find that WAEMUmembers have more or less the same business cycle. For sustainability and more open economies, itis imperative that WAEMU member countries respect the macroeconomic convergence criteria and also build productive capacities. It is also crucial to complete the West African Rail Loop Project tostrengthen regional integration.
Keywords: Africa, West; Afrika, Batı; Batı Afrika Devletleri Ekonomik Topluluğu; Bölgesel entegrasyon; Currency Union; Economic Community of West African States; Economic integration; Ekonomik entegrasyon; Ekonomik ve Parasal Birlik; Gravity Model; Monetary policy; Monetary unions; Para BirimiBirliği Economic and Monetary Union; Para birlikleri; Para birlikleri - Afrika, Batı; Para politikası; RegionalIntegration; Ticaret; Trade; WAEMU; Yerçekimi Modeli